Public Libraries: Essential Infrastructure for the Public Humanities - Podgajny, Stephen (Maine Policy Review, 2015)
Public libraries are a key component in the delivery of local humanities programs in Maine. Stephen Podgajny, executive director of the Portland (Maine) Public Library, outlines how public library infrastructure and resources support the humanities as collectors of humanities-related material, conveners and presenters of humanities programs, as collaborators with other humanities organizations, and as conservators of local historical collections. The author also discusses the future of public humanities and public libraries.